Potencial osteocondutor de grânulos de hidroxiapatita em defeitos críticos na calvária de ratos - Teixeira, Leonardo Jorge Carvalho (2009)
The biomaterials based on calcium phosphate are widely used as bone substitutes. The purpose of this study was to evaluate the osteoconductive potential of hydroxyapatites with different physicochemical characteristics, one with low crystallinity (AH-1) and another with high crystallinity (HA-2) inserted into criticalsized bone defects of rat calvaria. A total of 45 rats being 15 grafted with HA-1, 15 with HA-2 and 15 completed only by the clot. The sacrifice of animals (n = 5 per group) occurred in 1, 3 and 6 months after surgery and histotechnical and histomorphometric procedures were performed to determine the volume density of newly formed bone in the peripheral, intermediate and central regions of the defects for the three groups. The first analysis compared the volume density of newly formed bone in the three regions between the groups. The second evaluated the dynamics of bone formation in each group separately. When comparing the groups HA-1, HA-2 and clot, did not exist statistically significant differences in the volume density of newly formed bone between the peripheral, intermediate and central regions in the periods analyzed. However, analyzing the groups separately, there was difference in the dynamics of bone formation. The clot group presented an increase in the volume density of newly formed bone in the intermediate region at 6 months after surgery. The groups grafted with HA-1 at 3 months and HA-2 at 1 and 6 months after surgery showed equivalent volume density of newly formed bone in the peripheral, intermediate and central regions without difference statistically significant, demonstrating satisfactory osteoconductive potential.